Incidence and Frequency Rate of Cardiac Pacemaker Insertions in an Ageing Population - Asad Khan, Malik Faisal Iftekhar, Muhammad Shahid, Muhammad Kamran, Muhammad Bin Tashfeen, Bilal Mustafa (Pakistan Journal of Medical & Health Sciences, 2022)
Objective:The purpose of this study is to determine the incidence and frequency rate of cardiac pacemaker insertions in an ageing population. Study Design:Observational study Place and Duration: Conducted at Hayatabad Medical Complex Peshawar during from March, 2019 to August, 2019. Methods: There were 210 patients of both genders had ages >20 years were presented in this study. All the included patients had cardiovascular disease were hospitalized.After obtaining informed written permission, the demographics of enrolled patients included age, sex, BMI, comorbidities, education status, and place of residence.Incidence of cardiac pacemaker insertions among cases was determined. Frequency of PPM among all cases was recorded among sex and different age groups. SPSS 23.0 was used to analyze all data. Results:In our study, males were higher in numbers 130 (61.9%) than females 80 (38.1%). Included patients had mean age 71.8±11.56 years with mean BMI 25.4±11.42 kg/m2. There were 170 (80.9%) patients married and 150 (71.4%) cases were from urban areas. We found HTN was the most common comorbidity followed by diabetes mellitus and hyperlipidemia. We found that incidence rate of pace maker (PM) among patients with ages >75 years were higher found in 115 (54.8%) cases. Frequency of double chamber and triple chamber pacing was found in 98 (46.7%) cases. Frequency of cardiac resynchronization defibrillator was found in 120 (57.1%) cases. Conclusion:We concluded thatageing has a direct impact on the need for cardiac pacing, resulting in increased rates of incidence and prevalence. A growing number of elderly people will require electrophysiology and pacing services.